Assessment of Cargo Distribution Efficiency in Türkiye with Data Envelopment Analysis (DEA) (Third Sector Social Economic Review, 2026)
This study aims to assess the relative efficiency of firms in Türkiye’s cargo distribution sector using the Data Envelopment Analysis (DEA) method. DEA is a widely recognized approach for measuring efficiency, supported by academic communities and applicable in various fields.  In the analysis, seven variables were considered, encompassing six leading firms in the sector and one additional firm representing relatively minor companies. Within the scope of the study, all variables were transformed into percentages. While the number of employees, branches, and customer complaints were considered, the output variables focused on the amount of cargo transported and revenue generated. The efficiency analysis was conducted under the assumption of variable returns to scale, employing the Malmquist DEA model with an output-oriented approach over multiple years. Upon reviewing the results, it was determined that two or three firms demonstrated efficiency in each of the periods. In contrast, the remaining firms exhibited inefficiencies due to various issues, including customer shifts between companies. Inefficient firms faced challenges in operational, personnel, and technical efficiencies; firms that solve these problems are more efficient. The study contributes to the literature and the sector by providing policy recommendations for increasing efficiency and productivity in the Turkish cargo sector.
Keywords: Cargo; Distribution; DEA; Efficiency; Total Factor Productivity